DEVELOPING CURRICULUM OF THE DEPARTMENT OF ISLAMIC RELIGIOUS EDUCATION IAIN LHOKSEUMAWE ACEH - Aida Hayani (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Abstract: The curriculum is the most important component for developing the quality of Islamic Religious Education (IRE) in universities. The curriculum is a unique characteristic of a college compared to other universities. Nonetheless, the Government has provided guidelines for how the university curriculum is developed. This study aims to describe the development of IRE curriculum in IAIN Lhokseumawe Aceh. The research findings are as follows: first, the emphasis on curriculum development (a) clarity profile of graduates with a description of its operation. (b) The learning outcomes as an indicator graduate profile that refers to Indonesian Qualifications Framework (IQF) and National Standards for Higher Education (NSHE). (c) Field studies as a strategic issue which combined with the development of the course learning outcomes, (d) curriculum development in Department of Islamic Religious Education (IRE) also stressed on the aspect of IRE consisting of Al-Qur’an-Hadith, Aqidah Akhlak, Fiqh, and History of Islamic Culture to improve the professional competence of future teachers.